ASSESSMENT OF PROGRESS AND STATUS OF DATA ASSIMILATION IN NUMERICAL WEATHER PREDICTION - Kwon, In-Hyuk; English, Stephen; Bell, William; Potthast, Roland; Collard, Andrew; Ruston, Benjamin (Bulletin of the American Meteorological Society, 2018)
INTERNATIONAL WORKSHOP ON REAL-TIME NWP FORECAST SYSTEM What: Representatives from major operational centers and research institutes, including ECMWF, the Met Office, Météo-France, DWD, KMA, CMA, JMA, ECCC, NOAA/NCEP, NOAA/ESRL, NRL, NASA, and NCAR, gathered to discuss recent developments in real-time numerical weather prediction systems, especially data assimilation. Andrew Collard [National Oceanic and Atmospheric Administration (NOAA)/National Centers for Environmental Prediction (NCEP)] presented recent changes in NCEP’s NWP data assimilation configuration, including the introduction of four-dimensional ensemble-variational DA (4DEnVar). The concept of the German Weather Service [Deutscher Wetterdienst (DWD)]’s NWP model is an integrated system, including a nowcasting ensemble prediction system (EPS), Rapid Update Cycle (RUC) DA, and short-range NWP (Roland Potthast, DWD), where boundary conditions are provided by DWD’s global Icosahedral Nonhydrostatic (ICON)-EPS model based on the hybrid LETKF plus EnVar DA. The data volumes being read and written, archived, and communicated between processors is now very high. [...]efficient and innovative methods for input/out (I/O) are needed, such as parallel and asynchronous I/O, and dedicated I/O servers, alongside efforts to improve the scalability of core systems.